Employment Profile of English Speakers in Nord-du-Québec - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Nord-du-Québec’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Nord-du-Québec’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Profil d'emploi des Québécois d'expression anglaise au Nord-du-Québec - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise du Nord-du-Québec en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise de la région. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique du Nord-du-Québec, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.